Visualisation of relevant, satellite and emerging terms associated with academic references on Social Economy and relations with sustainability - Alarcón, Miguel Ángel; Álvarez, Juan Fernando; Morais, Leandro [UNESP] (Ministerio de Trabajo y Economia Social, 2022)
The Social Economy (SE) brings together economic practices carried out by for-profit and non-profit organisations in territories that express the diversity of cultural logics that differentiate them from the internal and external actions of traditional capital entities. This polyvalence generates a challenge to identify and consolidate an area of study with as common a perimeter as possible. In fact, in the consolidation of HE studies and in regular academic events there is always a section that demands contributions that narrow down a definition of common principles, aware that the generally accepted conception shows complementary principles, which concludes in several signifiers for a similar meaning. Thus, the intention to differentiate the components of the SE from the capitalist tradition continues to be generated, while at the same time generating interesting debates on the differentiation of its component families, which, however, sometimes try to move away from the search for common elements that place them within the whole. As a result, synergy initiatives between the SE’s component entities are held back, due to a problem of identification of entities that can lead to the containment of public policies for the promotion, maintenance and acceleration of the action of the SE. The inflation of titles, meanings and signifiers on relations between the Social Economy and sustainability does not contribute to a delimitation of practices that contribute to their analysis, both in aggregate and individually, since on many occasions sustainability is understood as an inherent attribute of these organisations and the case studies deal mostly with the elements that contribute and not those that would subtract in the assessment of overall sustainability. Thus, this paper seeks to contribute to the organisation of the academic literature on HE and its relationship to sustainability by analysing the academic output in Scopus through Social Network Analysis and Graph Analysis. The networks are configured on a thesaurus designed with a consensual set of terms specific, implicit, satellite and/or collateral to HE, on which significant relationships are inferred, materialised in the Scopus reference pool. It shows a strong increase in global research on the SE in the last 20 years with respect to the total average growth and an increase in the weight of academic literature on the components and principles of the SE, as well as that of emerging economic paradigms: Circular Economy, Green Economy, Corporate Social Responsibility, Collaborative Economy, among others. At the same time, a certain geographical specialisation can be detected. In addition, and since 2015, references to sustainability and those related to the Sustainable Development Goals (SDGs) have increased significantly. The method and results presented are sufficient to show what was intended: to offer a generic, panoramic concatenation of a definition of common principles of the ES construct with its components, with possible measurements of its impact and with the evaluation of the impact of public policies in different countries. However, it would need more space to incorporate complementary analysis alternatives that draw more knowledge from the reference pool of the exploited database.
Visualización de términos relevantes, satélites y emergentes asociados a las referencias académicas sobre Economía Social y relaciones con la sostenibilidad
Keywords: Non-Profit Sector; Social Economy; Social Network Analysis; Sustainability; Sustainable Development Goals